Environmental management plan (EMP) - Zawani, Zuwairi Izwan; Abd Slam Alsonosi, AlShrif; Zainol Abidin, Izzatul Ashikin; Fadzil, Norzubaidah; Othman, Nur Asmaliza; Fettysha, Suhana (Penerbit UTHM, 2020)
In order to achieve a target on resource conservation and pollution reduction thus Environmental Management Plan (EMP) was introduced. An EMP is a site or project specific plan developed to ensure that appropriate environmental management practices are followed during a project’s construction and/or operation. Use of this guideline will improve the contribution that an EMP can make to the effectiveness of the EIA process and assists in ensuring that commitments made in project’s EIA are implemented. This EMP Guideline was developed in consultation with government agencies, contractors and industry groups. The EMP improve the need for the future-monitoring programme. In implementing the EMP, the project proponents need to adhere to the Terms and Conditions of Environmental Regulation and Guidelines. The monitoring of environmental parameters during the construction and operation phases of the project enables the project development to be implemented within safe environmental conditions.